Muscle Relaxant and Sedative-Hypnotic Activities of Extract of Viola betonicifolia in Animal Models Supported by Its Isolated Compound, 4-Hydroxy Coumarin - Naveed Muhammad; Mohammad Saeed; Haroon Khan; Achyut Adhikari; Khalid Mohammed Khan (Journal of Chemistry)
The crude methanolic extract of the whole plant of Viola betonicifolia (VBME) was investigated for anxiolytic, muscle relaxant, sleep induction, antidepressant, and sedative activities) to ascertain its scientific values. VBME showed a significant (P<0.05) dose dependent anxiolytic action in staircase test. In muscle relaxant paradigms, a dose dependent muscle relaxation was observed. For phenobarbitone sleep induction test, VBME notably (P<0.05) reduced the latency time and increased total sleeping duration. Our tested extract was found free of any antidepressant activity, while the movement was significantly (P<0.05) shortened in locomotor activity. The whole plant of V. betonicifolia led to the isolation of 4-hydroxyl coumarin (4HC) which showed substantial safety profile in acute toxicity test. When challenged in Traction and Chimney tests, it showed significant (P<0.05) muscle relaxant effect in both muscle relaxant paradigms at 20 and 30 mg/kg during various assessment times. Nevertheless, 4HC was devoid of sedative and hypnotic potentials. In conclusion, VBME had strong muscle relaxant and sedative-hypnotic properties, while its isolated compound, 4HC, possessed a significant muscle relaxant action with substantial safety profile without sedative-hypnotic effects.